Changes in collegiate ice hockey player anthropometrics and aerobic fitness over 3 decades - Triplett, A. N.; Ebbing, A. C.; Green, M. R.; Connolly, C, P.; Carrier, D. P.; Pivarnik, J. M. (Applied Physiology, Nutrition, and Metabolism, 2018)
Over the past several decades, an increased emphasis on fitness training has emerged among collegiate ice hockey teams, with the objective of improving on-ice performance. However, it is unknown if this increase in training has translated over time into changes in the anthropometric and fitness profiles of collegiate ice hockey players. The purposes of this study were to describe anthropometric (height, weight, body mass index (BMI), percent body fat (%fat)) and aerobic fitness (peak oxygen consumption) characteristics of collegiate ice hockey players over a period of 36 years and to evaluate whether these characteristics differ among player positions. Anthropometric and physiologic data were obtained through preseason fitness testing of players (N = 279) from a National Collegiate Athletic Association Division I men`s ice hockey team from the years 1980 through 2015. Changes over time in the anthropometric and physiologic variables were evaluated via regression analysis using linear and polynomial models, and differences among player positions were compared via ANOVA (p < 0.05). Regression analysis revealed that a cubic model best predicted changes in mean height (R2 = 0.65), weight (R2 = 0.77), and BMI (R2 = 0.57), whereas a quadratic model best fit change in %fat by year (R2 = 0.30). Little change was observed over time in the anthropometric characteristics. Defensemen were significantly taller than forwards (184.7 ± 12.1 vs. 181.3 ± 5.9 cm) (p = 0.007), and forwards had a higher relative peak oxygen consumption compared with defensemen (58.7 ± 4.7 vs. 57.2 ± 4.4 mL/kg·min) (p = 0.032). No significant differences were observed in %fat or weight by position. Although average player heights and weights fluctuated over time, increased emphasis on fitness training did not affect the athletes` relative aerobic fitness. Differences in height and aerobic fitness levels were observed among player positions.